2022
DOI: 10.1136/jitc-2021-004374
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of body mass index in patients with advanced NSCLC treated with chemoimmunotherapy combinations

Abstract: IntroductionIt has been recognized that increasing body mass index (BMI) is associated with improved outcome from immune checkpoint inhibitors (ICIs) in patients with various malignancies including non-small cell lung cancer (NSCLC). However, it is unclear whether baseline BMI may influence outcomes from first-line chemoimmunotherapy combinations.MethodsIn this international multicenter study, we evaluated the association between baseline BMI, progression-free survival (PFS) and overall survival (OS) in a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In addition, the nutritional status of patients is also an important factor affecting tumor progression. Pre-treatment BMI and albumin levels will affect the prognosis of patients with lung cancer (30)(31)(32). As a new type of nutrition monitoring index, PNI is composed of albumin and lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nutritional status of patients is also an important factor affecting tumor progression. Pre-treatment BMI and albumin levels will affect the prognosis of patients with lung cancer (30)(31)(32). As a new type of nutrition monitoring index, PNI is composed of albumin and lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…After detailed evaluations, 183 studies were excluded because of cut-off values, outcomes, unavailable HR data, or other reasons. Ultimately, nine studies, including 4602 NSCLC patients treated with ICIs, were selected for this metaanalysis [14][15][16][17][18][19][20][21][22] .…”
Section: Literature Searchmentioning
confidence: 99%
“…All nine studies reported the association between BMI and PFS [14][15][16][17][18][19][20][21][22] . The low BMI group included underweight patients (BMI < 18.5 kg/ m 2 ) and normal patients (18.5 ≤ BMI ≤ 24.9 kg/m 2 ).…”
Section: Progression-free Survival For All Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity-associated in ammation dysregulates immune response, potentially leading profound effects on the toxicity and e cacy of ICIs. Body mass index (BMI) is clinically used to assess body fat in human subjects ( 6 , 7 ). Past studies declared a positive prognostic role of high BMI in NSCLC patients treated by rst-line single agent ICIs-based regimens, whereas con ict result was obtained in the chemoimmunotherapy combinations (6-8 ).…”
mentioning
confidence: 99%